معوقات الشراكة المجتمعية في مجال البحث العلمي في الجزائر - خلفاوي, عزيزة (جامعة الوادي - University of Eloued, 2020)
يعد موضوع الشراكة بين المجتمع و الجامعة ضرورة ملحة و آنية في المجتمع الجزائري اقتضته ضرورات التطور العلمي المتسارع، ووظيفته في حل مشكلات المجتمع، و يشير الواقع الجزائري من خلال العديد من الدراسات غياب ملحوظ لهذه الشراكة إذ تقتصر وظيفة الجامعة حاليا في التدريس، وإنتاج البحث العلمي، أما وظيفة خدمة المجتمع فهي غائبة نظرا لوجود معوقات لذلك.بناء على أهمية هذا الموضوع نهدف في مقالنا هذا إلى الإجابة على التساؤل التالي: ماهي معوقات الشراكة المجتمعية في مجال البحث العلمي في الجزائر؟ ولقد ركزنا في إجابتنا على إبراز معوقين أساسين هما إشكالية مفهوم الشراكة المجتمعية، ومعوقات تتعلق بالبحث العلمي نفسه، وفي الأخير خلصنا إلى مقترحات للموضوع. Abstract: The partnership between society and the university is an urgent topic in the Algerian society that is dictated by both the necessities of accelerated scientific development and its function in solving the problems of society. However, research to date indicates a visible absence of this partnership since the university's job is currently limited to only teaching and producing scientific research. As for the function of community service, it is absent because of some obstacles. Due to the importance of this topic, the present article intends to answer the following question: What are the obstacles of community partnership in the field of scientific research in Algeria? In response to this question, two basic disabilities are highlighted: the problem of the concept of community partnership and obstacles related to scientific research itself. The article concludes with suggestions related to the topic.
مقال
Keywords: معوقات؛ شراكة مجتمعية؛ بحث علمي; Obstacles; community partnerships; scientific research